2009
DOI: 10.1080/00207450802324861
|View full text |Cite
|
Sign up to set email alerts
|

Executive Functioning and the Two-Factor Model of Psychopathy: No Differential Relation?

Abstract: There are indications that the interpersonal affective factor and the social deviation factor, both of which are underlying dimensions of psychopathy, have a positive and a negative relationship, respectively, with executive functioning. However, this is seldom taken into consideration in the research on the relationship between executive functioning and psychopathy, which may be an explanation for the many inconsistent results in this area as reported in the literature (e.g., Rogers, 2006). In the present stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 24 publications
0
10
1
Order By: Relevance
“…Conversely, FD was associated with better EF as reflected by the composite score and was unrelated to response inhibition. Mol and colleagues found that in an inpatient forensic sample, AI was related to worse EF while FD was related to better EF (Mol, Van Den Bos, Derks, & Egger, 2009). Recent reviews have indicated a mixed pattern of findings with regard to these relationships, one concluding that there is no clear association between the interpersonal-affective trait and EF (Baskin-Sommers et al, 2015) or that EF deficits in those with psychopathic traits exist primarily in individuals who are incarcerated compared to those who are not (Gao & Raine, 2010), while another that the evidence is inconsistent for both traits (Maes & Brazil, 2013).…”
Section: Introductionmentioning
confidence: 94%
“…Conversely, FD was associated with better EF as reflected by the composite score and was unrelated to response inhibition. Mol and colleagues found that in an inpatient forensic sample, AI was related to worse EF while FD was related to better EF (Mol, Van Den Bos, Derks, & Egger, 2009). Recent reviews have indicated a mixed pattern of findings with regard to these relationships, one concluding that there is no clear association between the interpersonal-affective trait and EF (Baskin-Sommers et al, 2015) or that EF deficits in those with psychopathic traits exist primarily in individuals who are incarcerated compared to those who are not (Gao & Raine, 2010), while another that the evidence is inconsistent for both traits (Maes & Brazil, 2013).…”
Section: Introductionmentioning
confidence: 94%
“…A study by Lapierre, Braun, and Hodgins (1995) However, the literature regarding the relationship between executive functioning and psychopathy as a whole is somewhat mixed (Hansen, et al, 2007;Ishikawa, Raine, Lencz, Bihrle, & Lacasse, 2001;Maes & Brazil, 2013;Mol, Van den Bos, Derks, & Egger, 2009;Pham, Vanderstukken, Philippot, & Vanderlinden, 2003; D. Rogers, 2006). A study using a dichotic listening task showed abnormal processing asymmetries for psychopaths (Hiatt, Lorenz, & Newman, 2002), this was primarily found on complex tasks involving emotional targets.…”
Section: Cognitive and Executive Functionsmentioning
confidence: 99%
“…Overall is the available literature regarding psychopathy and executive functioning somewhat mixed (Maes & Brazil, 2013;Mol, et al, 2009;Pham, et al, 2003;R. D. Rogers, 2006), and one problem is that few studies have examined the separate contribution of the two PCL-R factors.…”
Section: "Construct Drift"mentioning
confidence: 99%
“…Given the heterogeneity and complexity of the psychopathy construct, it has been suggested that studies should further distinguish between subtypes or specific traits of psychopathy in relation to decision making, so the aforementioned scientific inconsistencies could be better explained [28]. For example, some researchers reason that risky decision making would be primarily related to aspects of an antisocial and impulsive lifestyle [17,29] (factor two of the Hare construct). Also, a specific relation between risky decision making and callous unemotional traits (factor one of the Hare construct) has been suggested [30], presumably due to amygdala malfunctioning [7,31,32].…”
Section: Introductionmentioning
confidence: 99%